11. xyz - xy - yz - zx + x + y + z - 1
12. xy(x + y) + yz(y + z) + zx(z + x) + 2xyz
13. xy(x + y) + yz(y + z) + zx(z + x) + 3xyz
giúp mik vs mik đang cần gấp =(((
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(xyz-xy-yz-zx+x+y+z-1\)
\(=\left(xyz-xy\right)-\left(yz+zx\right)+\left(x+y\right)+\left(z-1\right)\)
\(=xy\left(z-1\right)-z\left(x+y\right)+\left(x+y\right)+\left(z-1\right)\)
\(=[xy\left(z-1\right)+\left(z-1\right)]-[z\left(x+y\right)-\left(x+y\right)]\)
\(=\left(z-1\right)\left(xy+1\right)-\left(x+y\right)\left(z-1\right)\)
\(=\left(z-1\right)[\left(xy+1\right)-\left(x+y\right)]\)
\(=\left(z-1\right)\left(xy+1-x-y\right)\)
\(x^2-4xy-z^2+4y^2\)
\(=\left(x^2-4xy+4y^2\right)-z^2\)
\(=\left(x-2y\right)^2-x^2\)
\(=\left(x-2y-z\right)\left(x-2y+z\right)\)
`x^2 - 4xy-z^2 +4y^2=(x^2 - 2.x.2y +(2y)^2) - z^2=(x-2y)^2 - z^2=(x-2y-z)(x-2y+z)`
x^2-2x+1-y^2=(x^2-2x+1)-y^2
=(x-1)^2-y^2
=(x-1-y).(x-1+y)
x4 - 2x3 + x2 - 2x
= x3(x - 2) + x(x - 2)
= (x - 2)(x3 + x)
= (x - 2)(x + 1)(x2 - x + 1)
`x^4 - 2x^3 +x^2 - 2x=(x^4 - 2x^3)+(x^2 - 2x)=x^3 (x - 2)+x(x-2)=(x-2)(x^3 +x)=(x-2)x(x^3+1)=(x-2)x (x+1)(x^2 -x+1)`
\(^{x^2-x-6=\left(x^2-3x\right)+\left(2x-6\right)=x\left(x-3\right)+2\left(x-3\right)=\left(x-3\right)\left(x+2\right)}\)
x^2-x-6=x^2-3x+2x-6
=(x^2-3x)+(2x-6)
=x(x-3)+2(x-3)
=(x+2).(x-3)